ChemInform Abstract: New Synthetic Strategy for Chiral 2‐Oxazolidinones Derivatives via Rhodium‐Catalyzed Asymmetric Hydrogenation. Issue 22 (12th May 2016) - Wang, Qingli; Tan, Xuefeng; Zhu, Ziyue; Dong, Xiu‐Qin; Zhang, Xumu
Abstract: Cyclic enamido esters undergo asymmetric hydrogenation in the presence of the optically active rhodium catalyst (RCT) to form 2‐oxazolidinones in excellent yields with good enantioselectivities.